RETROSPECTION AS PROLOGUE - Gunner, Jeanne and McNenny, Gerri (Journal of Basic Writing, 1997)
When we approached Jeanne Gunner and Gerri McNenny about their possible contributions to this special issue, we didn't know if we should ask for something on the order of an introduction or something more like a postscript. It turns out they did a bit of both, composing separate but complementary pieces. We've decided to frontload them, though they are (as Jeanne's individual title suggests) afterthoughts. Jeanne Gunner, formerly of the UCLA Writing Program and now Core Composition Director at the Santa Gara University, Chair of the Conference on Basic Writing from 1995-1997, offers the unusual opportunity of examining the mottoes, personal and professional, for mounting such an enterprise as the workshop represents. Co-Chair of Conference on Basic Writing, Gerri McNenny is Director of Composition at the downtown campus of the University of Houston and is hard at work on an anthology of essays treating mainstreaming vs. tracking BW students; she chooses to highlight the issue of class, certainly the prominent note struck that day (perhaps because it seemed relatively undernoticed before), and her discussion provides an excellent overview of and introduction to the presentations of the other participants.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzQ0NDAyMQ